2002
DOI: 10.1007/s00294-002-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of a G protein α subunit gene results in reduced pathogenicity in Fusarium oxysporum

Abstract: The cloning of fga1, the gene encoding a G protein alpha subunit, was performed by standard PCR techniques and by screening a Fusarium oxysporum genomic library, using the PCR product as a probe. The full-length open reading frame spanned 1,059 nucleotides and the deduced primary structure of the protein (353 amino acid residues) showed high identity to those of G protein alpha(i) family proteins from other filamentous fungi. Disruption of fga1 had no effect on vegetative growth, but reduced the conidiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 22 publications
6
115
0
6
Order By: Relevance
“…Similar to MgGpa1, the orthologous group I G␣ proteins in C. parasitica, M. grisea, Stagonospora nodorum, F. oxysporum, Colletotrichum trifolii, and B. cinerea affect pathogenicity (7,16,28,41,61,65), whereas the orthologous proteins CGA1 and GPA1 in Cochliobolus heterostrophus and U. maydis, respectively, are dispensable for pathogenicity (24,57). Such a functional dichotomy was also observed for group III G␣ orthologs.…”
Section: Vol 8 2009mentioning
confidence: 77%
See 3 more Smart Citations
“…Similar to MgGpa1, the orthologous group I G␣ proteins in C. parasitica, M. grisea, Stagonospora nodorum, F. oxysporum, Colletotrichum trifolii, and B. cinerea affect pathogenicity (7,16,28,41,61,65), whereas the orthologous proteins CGA1 and GPA1 in Cochliobolus heterostrophus and U. maydis, respectively, are dispensable for pathogenicity (24,57). Such a functional dichotomy was also observed for group III G␣ orthologs.…”
Section: Vol 8 2009mentioning
confidence: 77%
“…We observed that all M. graminicola strains were equally thermosensitive, whereas for N. crassa and F. oxysporum, thermotolerance was observed in G␣-encoding mutants and was positively correlated with decreased intracellular cAMP levels (28,29,71). Indeed, constitutive expression of Gna1 in N. crassa resulted in elevated cAMP levels and increased thermosensitivity (26,71).…”
Section: Vol 8 2009mentioning
confidence: 77%
See 2 more Smart Citations
“…Mitogen-activated protein kinase (MAPK) and cAMP protein kinase A (cAMP-PKA) signal transduction systems control important steps during plant infection. Some MAPK genes, such as Fmk1 , Fga1 and Fgb1, of F. oxysporum play significant roles in the pathogenicity (Di Pietro et al 2001; Jain et al 2002, 2003). RNA-silencing pathways regulate the MAPK and the cAMP-PKA cascades to affect virulence in F. oxysporum at the stage of infection.
10.1080/21501203.2015.1027313-F0005Figure 5.Pathogenicity of wild-type Fusarium oxysporum strain A8 and the Δ Qip mutant.
…”
Section: Resultsmentioning
confidence: 99%